The Effectiveness of Minang Mart Partnership Pattern in Empowering Local Micro, Small, and Medium Enterprises in West Sumatra - Rendi Febria Putra; Kismartini Kismartini; Retno Sunu Astuti (Jurnal Administrasi Publik (Public Administration Journal), 2022)
This article aims to discuss the effectiveness of the Minang Mart partnership pattern in empowering local Micro, Small, and Medium Enterprises in Padang City, West Sumatra. The problem is focused on the realization of Minang Mart's idea for empowerment and collaboration with local traders and MSMEs. Along with its development, Minang Mart has come out of the initial idea, namely the modernization and empowerment of local traders, and local Micro, Small, and Medium Enterprises have not been implemented until now. To approach this problem, Nugroho's theoretical reference was used regarding the effectiveness of a policy which was put forward in four "right" ways, namely the right policy, the right implementer, the right target, and the right environment. The data were collected through observation and documentation techniques. This study was qualitative research with a descriptive approach and inductive analysis. This study concludes that based on the four "correct" policies in the effective study of policies, the West Sumatra government was not ready with what was announced and it was known that the policies regarding Minang Mart have not been implemented effectively. Minang Mart's policy was the right policy and has not fulfilled the right implementation, right target, and environmental aspects. It is known that Minang Mart is currently managed by the private sector, Minang Mart's partnership with local Micro, Small, and Medium Enterprises has not materialized, and there are no zoning regulations regarding the establishment of Minang Mart.